Advice on beans: Farmerline's Mergdata farm-advice service in Ghana ICTs - Sakyi, Patrick; Abdul-Fatawu, Mohammed (Technical Centre for Agricultural and Rural Cooperation, 2017)
Farmerline provides users with farm advice, weather forecasts, market information messages on mobile phones in local languages. The same software allows organizations to conduct surveys of farms and farmers. A series of training courses taught users how it works.